2018
DOI: 10.3389/fmars.2018.00239
|View full text |Cite
|
Sign up to set email alerts
|

Seafood Trade Routes for Lobster Obscure Teleconnected Vulnerabilities

Abstract: Reliance on international seafood markets leaves small-scale fishers and fishing economies vulnerable to distant disturbances that can negatively affect market prices and trigger social, economic, and environmental crises at local levels. This paper examines the role of seafood trade routes and re-exports in masking such market linkages. We employ a network approach to map the global trade routes of lobster (Homarus spp.) from small-scale producers in North America to terminal markets and evaluate the extent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…Many coastal communities in the region have strong economic and cultural ties to fishing [26,27]. However, many fisheries and fishing communities in the Northeast have suffered recent shocks related to trade policy and other economic factors, overfishing, natural disasters, climate change, and other drivers [28][29][30]. For example, commercial fisheries in New York and New Jersey were hard hit by Hurricane Sandy and its aftermath in 2012 and were subsequently declared federal fishery disasters later that year [31,32].…”
Section: Resilience Of Fisheries Systemsmentioning
confidence: 99%
“…Many coastal communities in the region have strong economic and cultural ties to fishing [26,27]. However, many fisheries and fishing communities in the Northeast have suffered recent shocks related to trade policy and other economic factors, overfishing, natural disasters, climate change, and other drivers [28][29][30]. For example, commercial fisheries in New York and New Jersey were hard hit by Hurricane Sandy and its aftermath in 2012 and were subsequently declared federal fishery disasters later that year [31,32].…”
Section: Resilience Of Fisheries Systemsmentioning
confidence: 99%
“…This question is especially important to consider given that there are well-known risks associated with the globalization of markets. For example, global markets can drive resource overexploitation and extirpating of local stocks (Berkes et al 2006 ), disincentivize local governance (Basurto et al 2013 ), create dependencies on expensive fishing and shipping technologies (Perry et al 2011 ), disrupt local markets (Robards and Greenberg 2007 ), mask local ecological decline (Deutsch et al 2007 ), and make coastal communities vulnerable to shocks in other places (Liu et al 2013; Stoll et al 2018 ). This latter point was driven home in the lobster fishery the following year.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, the United States traded $254 million worth ($367 million adjusted for inflation) of lobster to just over 50 countries in 2001 (United Nations 2021 ). In recent years, markets in Asian have become particularly important, surpassing Europe as the second most important trade region outside North America 1 (Stoll et al 2018 ). These markets have been established through private and public investment in marketing, infrastructure, and technology, including state sponsored trade missions and grant funding to support domestic processing and storage facilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example,Gómez and Lien (2017) have previously observed that the global financial crisis of 2007-2008 played a critical role in catalyzing local food distribution in southern Europe. Similarly, during the 2007-2008 global financial crisis, the iconic lobster fishery in Maine, which had been becoming progressively more globalized(Stoll et al, 2018), pivoted their efforts toward local and domestic seafood distribution. Likewise, this pattern of food systems localization has also been reported to us anecdotally from multiple Latin American locales during the pandemic, including Puerto Rico(Marco Hanke, pers.…”
mentioning
confidence: 99%